A Systematic Literature Survey, Research Challenges and Future Directions of Image Processing Algorithms in Solar Tracking System: Enhancing efficiency and reliability in solar energy - Mahalle, Avinash G.; Deshmukh, S. M. (Johnson Matthey technology review, 2025)
Solar power is the primary renewable energy solution for alleviating power shortages in developing areas. Leveraging this energy faces constraints arising from specific environmental conditions. Challenges in solar tracking systems include maintaining accuracy under varying environmental conditions, such as changes in sunlight, weather shadows and ensuring reliable performance while minimising energy consumption and mechanical wear. To address these challenges, solar tracking technology is employed. Solar trackers are pivotal in optimising power generation from photovoltaic panels, offering a range of drive types and control strategies to enhance efficiency. This review aims to explore various solar tracking systems to improve the efficiency of solar power generation. We compare the tracking approaches, performance, advantages and disadvantages of different tracking systems. Additionally, this review presents and categorises various types of solar tracking systems according to the technologies and methods of operation, focusing primarily on image processing-based solar tracking systems. Utilising image processing technology in solar tracking systems provides innovative approaches to enhance energy generation from photovoltaic panels. These techniques enable precise detection of the sun’s position, even under challenging environmental conditions, ultimately enhancing efficiency and reliability.